Man, fate, and death in Indo-European tradition (Letras Clássicas, 2004)
This paper deals with Indo-European concepts concerning the human condition: the nature of man, the role of fate in shaping his life, his destiny in death. The evidence is partly drawn from linguistic material, partly from literary. The assumption is that, just as comparison of vocabulary in widely separated languages such as Hittite, Sanskrit and Old Irish makes it possible to reconstruct words of the parent language, so comparison of parallel motifs in different traditional literatures may show up inherited ideas and beliefs.